Die Judenbuche and the "Judens‐buch": Hermeneutic Hindrance and Scriptural Reading in Droste‐Hülshoff's Crime Novella. (July 2016) - Almog, Yael
Abstract : The article presents Annette von Droste‐Hülshoff's Die Judenbuche as a reaction to the disjunction between textual interpretation and confessional belonging in modernity. I argue that the epicenter of this critique is the insertion of a Hebrew sentence that embodies both in its language and in its content—talion law—the word of the Bible as a legal authority. Appearing in the midst of the novella, the biblical language creates a "hermeneutical hindrance, " and signals the reliance of interpretation on religious training of scriptural reading. Die Judenbuche thus alerts to the codependence of hermeneutical practices and moral codes. The article concludes that in the novella, the adherence of the village's Jews to the language of the Bible hints that confessional difference may subtend diverging cultures of interpretation and perpetuate the distinct moral codes that they convey.